Melatonin treatment of repetitive behavioral deficits in the Cntnap2 mouse model of autism spectrum disorder - Huei Bin Wang; Yu Tahara; Shu Hon Christopher Luk; Yoon-Sik Kim; Olivia N. Hitchcock; Zoe A. MacDowell Kaswan; Yang In Kim; Gene D. Block; Cristina A. Ghiani; Dawn H. Loh; Christopher S. Colwell (Neurobiology of Disease, 2020)
Nighttime light pollution is linked to metabolic and cognitive dysfunction. Many patients with autism spectrum disorders (ASD) show disturbances in their sleep/wake cycle, and may be particularly vulnerable to the impact of circadian disruptors. In this study, we examined the impact of exposure to dim light at night (DLaN, 5 lx) in a model of ASD: the contactin associated protein-like 2 knock out (Cntnap2 KO) mice. DLaN was sufficient to disrupt locomotor activity rhythms, exacerbate the excessive grooming and diminish the social preference in Cntnap2 mutant mice. On a molecular level, DLaN altered the phase and amplitude of PER2:LUC rhythms in a tissue-specific manner in vitro. Daily treatment with melatonin reduced the excessive grooming of the mutant mice to wild-type levels and improved activity rhythms. Our findings suggest that common circadian disruptors such as light at night should be considered in the management of ASD.